3D nanoarchitectures of α-LiFeO2 and α-LiFeO2/C nanofibers for high power lithium-ion batteries. (April 2015) - Büyükyazi, Mehtap; Mathur, Sanjay
Abstract: Hydrodynamic structuring of alkoxide-based sols in an electrical field is a promising technique to fabricate one-dimensional materials as free-standing fiber mats with high surface area and precisely controlled microstructure. Hollow α-LiFeO2 and composite α-LiFeO2 /C nanofibers were prepared as self-supported 3D architectures of ceramic fibers by single-step electrospinning of metal alkoxide sols. The spinel fibers exhibited a crystalline spinel phase with uniform fiber diameter and morphology that was modified by a thin sheath of amorphous carbon in the composite fibers that enhances the electrical conductivity and also has a structure-holding influence. The atomic scale mixing and pre-existing LiOFe units in the spinning solution were the delivers of observed phase purity and control over the surface properties verified by high resolution TEM data. Galvanostatic and potentiostatic studies confirmed the superior electrochemical behaviors of α-LiFeO2 and α-LiFeO2 /C nanofibers as high-energy density anode materials in half-cell configuration. α-LiFeO2 /C composite nanofibers showed after 50 cycles a discharge capacity of 821 mAh/g at 0.1 C with a capacity retention of 75% from the 2nd to 50th cycle, whereas the discharge capacity of α-LiFeO2 -hollow nanofibers was found to be 756 mAh/g with a capacity retention of 68%. Flexible composite nanofiber networks are promising solution enabling improved electronic and ionic conductivity and mechanical stability for the development of lithium-ion batteries with high power and energy densities. Investigations on the stability and rate capability of α-LiFeO2 /C-composite electrode studied at different rates of 0.1 C, 0.25 C and 0.5 C for 75 cycles also showed high capacity values that indicated their potential as anode materials. Graphical abstract: Self-supporting 3D Nanoarchitectures of α-LiFeO2 and α-LiFeO2 /C Nanofibers for High Power Lithium-Ion Batteries. Self-supported 3D architectures of hollow α-LiFeO2 and composite α-LiFeO2 /C nanofibers fabricated by coaxial electrospinning of metal alkoxide sols are high-energy density anode materials with superior electrochemical performance. Highlights: Fabrication of 3D electrode architecture for Li-ion batteries based on electrospun α-LiFeO2 and α-LiFeO2 /C composites. The experimental findings underscore that the synergic mechanisms in nanomaterials and nanocomposite often depend on the preparation methods and judicious choice of phase-forming elements. High discharge capacities of 756 mAh/g for α-LiFeO2 and 821 mAh/g for α-LiFeO2 /C were achieved.